Optimalisasi Peran Hukum dalam Pengembangan Pariwisata Pesisir Berkelanjutan sebagai Katalis Penerapan Ekonomi Biru di Indonesia - Salsabila Wahyu Aprilia; Nasya Nurul Amalina (CV Rewang Rencang, 2023)
As a country committed to the principles of blue economy, Indonesia must implement a sustainable paradigm in coastal tourism policies. This requires incorporating the triple bottom line concept by John Elkington which includes people, planet, and profit. This study employs a normative juridical method to analyze disparities in tourism development across regions and the inadequacy of existing regulations. Recommended indicators for evaluating legal system effectiveness are based on Lawrence Friedman's legal system theory consisting of legal structure, substance, and culture which aims to optimize sustainable coastal tourism and promote economic development rooted in the Blue Economy principles in Indonesia. Keywords: Blue Economy, Coastal Tourism, Law.